Stress Response and Analgesia During and after Robotic-Assisted Pelvic Exenteration - A. D. Lifanova; A. A. Grazhdankin; I. I. Lutfarakhmanov (Креативная хирургия и онкология)
Introduction. Thoracic epidural analgesia or thoracic epidural anaesthesia (TEA) and opioid-based intravenous multimodal analgesia (MMA) provide adequate control of perioperative pain, however, comparative data are still to be gathered. Aim. To compare both anesthesia techniques in terms of stress response during and after robotic-assisted pelvic exenteration (PE). Materials and methods. 112 patients were divided into 2 equal groups A level of serum cortisol was measured at induction of anesthesia and in 2, 24, and 48 hours. The efficacy of analgesia was compared using a 10-point numeric pain scale. Analgesic administration and side effects were reported for 1–3 postoperative days. Results. Cortisol levels increased 2 hours after skin incision in the MMA group and only in 24 hours in the TEA group (p < 0.050). Postoperative cortisol levels were significantly lower in the TEA group (p = 0.001). Numeric pain scores were significantly lower in the TEA group (1.7 [1.0–3.2] vs. 2.7 [2.1–4.2]; 1.9 [1.0–3.3] vs. 3.5 [3.5–5.0]; 3.7 [3.0–4.8] vs. 4.2 [3.7–4.7], respectively; p < 0.050). Patients in the TEA group received less opioid administration (4.3 mg vs. 13.9 mg; 7.0 mg vs. 19.9 mg; 10.9 mg vs. 16.5 mg, respectively; p < 0.050). The two groups of patients were detected with no significant difference in the incidence of respiratory depression. Discussion. According to the study results, perioperative stress response was reduced with TEA being added to the anesthesia protocol. Patients in the TEA group received lower doses of analgesics. Both groups produced similar short-term postoperative outcomes. Conclusion. As compared to opioid-based MMA, TEA provided more effective analgesia and similar side effect profiles. Therefore, TEA appears to be an acceptable method for stress response suppression and pain management in patients undergoing robotic-assisted PE.